LACTATE CONTENT, TOTAL POLYPHENOLS AND ANTIOXIDANT ACTIVITY OF SELECTED COMMERCIAL YOGURTS FROM THE SERBIAN MARKET - Popovic, Tamara; Pokimica, Biljana; Takić, Marija; Petrović Oggiano, Gordana; Debeljak Martačić, Jasmina; Šarac, Ivana; Glibetić, Marija (Food and Feed Research, 2022)
One of the most popular dairy products worldwide is yogurt, which flavor is highly influenced by lactic acid content. Yogurts with fruit preparations contain polyphenols, secondary plant metabolites with proven antioxidant properties. As there is no data regarding neither lactate nor polyphenol content in commercial yogurts in Serbia, this study aimed to determine lactate and polyphenol levels, as well as antioxidant activity in selected yogurts. A total of 15 plain and 5 fruit yogurts with strawberry preparations were analyzed. Lactate contents were from 0.83 to 1.33%. Three plain yogurts in plastic containers differed in lactate content. There was no difference in lactate content among the same plain yogurts packed in plastic and Tetra Pack containers. Fruit yogurts with strawberry preparations differed in total polyphenol content in the range from 6.84 to 29.11mg GAE/100 g and antioxidant properties were determined by reducing power test (from 0.22 to 0.79) and DPPH assay (from 28.13 to 87.23%), while there was no difference regarding lactate. Our results provided new information about the levels of lactate, total polyphenols and antioxidant activity of selected commercial yogurts available on the Serbian market.